Diseño de un pop-up store móvil para empresas online que funcione como un nuevo canal de comercialización (2019)
There are a lot of emerging entrepreneurship in the fashion sector in the city of Bogotá, of which there is a large percentage that chooses to market their products only online due to the high costs of leasing or selling commercial premises in the city, leading them to exhibition fairs, which only occur at certain times of the year. Through this project, we seek to provide a tool that allows these companies to strength relationships with their customers by generating an omnichannel sales system. This is how the “Inside The Box” entrepreneurship was born, which offers a design and rental service for mobile pop-up stores for a short period of time. These Pop up store are built on trailers whose exterior architecture is standardized, their interior furniture is customized, and the facade and some elements of their interior are personalized, offering customers the possibility of giving their buyers a unique experience and still being able to reuse the material and the structure of the store multiple times.